Tetrandrine sensitizes nasopharyngeal carcinoma cells to irradiation by inducing autophagy and inhibiting MEK/ERK pathway - Jun Wang; Zhouzhou Yao; Xiaoping Lai; Hongwei Bao; Yue Li; Shuaixiang Li; Lihong Chang; Gehua Zhang (Cancer Medicine)
Abstract Radioresistance was the main reason for local recurrence and metastasis of nasopharyngeal carcinoma. Tetrandrine is reported as an antitumor drug via inducing cell cycle arrest and apoptosis. In this study, the radiosensitization effects of maximum noncytotoxic doses of tetrandrine in nasopharyngeal carcinoma were analyzed both in vitro and in vivo, using MTT assay, western blot, TUNEL, and HE staining. It was found that the maximum dose of tetrandrine inhibited the phosphorylation of ERK and MEK induced by irradiation, and significantly enhanced irradiation‐induced cell growth inhibition in nasopharyngeal carcinoma cells CNE1, CNE2, and C666‐1. The ERK activator and overexpression of ERK reversed the radiosensitization effect of tetrandrine. About 50 mg/kg of tetrandrine which was used as the maximum noncytotoxic dose of tetrandrine in vivo, enhanced the radiosensitivity of the xenograft tumor and increased the apoptosis rate of the xenograft tumor cells caused by irradiation, while did not raise the side effect of the treatment. Moreover, tetrandrine increased autophagy in nasopharyngeal carcinoma cells. These results suggested that the maximum noncytotoxic dose of tetrandrine sensitized nasopharyngeal carcinoma to irradiation by inhibiting MEK/ERK pathway and inducing autophagy.